A review of reproductive performance of female Bos indicus (Zebu) cattle - Mukasa-Mugerwa, E. (International Livestock Centre for Africa, 1989)
Reviews the reproductive biology of cows with emphasis on Bos indicus (Zebu) cattle. Presents the reproductive anatomy and endocrinology of the cow. Examines changes that occur at puberty, during oestrous cycle and at pregnancy. Describes measures of reproductive performance, causes of infertility and how these can be diagnosed and their effects minimised. Also discusses the role of nutrition in cattle reproduction, lactational anoestrus and the effect of weaning and herd health programmes. Includes data from Africa, Asia, America and Australia.